2020
DOI: 10.20944/preprints202007.0393.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enterococci, from Harmless Bacteria to a Pathogen

Abstract: Enterococci are gastrointestinal commensals whose hardiness allowed them to colonize very diverse environments, including soils, water, food and feed. This ability to overcome adverse conditions makes enterococci problematic once they colonize hospital niches. Together with the malleability of their genomes, the capacity to acquire and disseminate determinants of antibiotic resistance have contributed to convert what was once just another opportunistic pathogen into a first-class clinical problem. This review … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…This is not surprising as enterococci are the third-highest common organisms in UTIs, and they also form part of the microflora in the gut of humans. 61 Studies that analyzed multiple clinical specimen isolated more VRE strains than studies that analyzed just one type of clinical specimen. The presence of enterococci in different clinical specimen can be attributed to their presence in the gut as normal flora and their ability to cause varieties of infections ranging from UTI to bacteremia to endocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising as enterococci are the third-highest common organisms in UTIs, and they also form part of the microflora in the gut of humans. 61 Studies that analyzed multiple clinical specimen isolated more VRE strains than studies that analyzed just one type of clinical specimen. The presence of enterococci in different clinical specimen can be attributed to their presence in the gut as normal flora and their ability to cause varieties of infections ranging from UTI to bacteremia to endocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…2014; Ramos et al . 2020). In contrast, Enterococcus species are also one of the main Gram‐positive microorganisms associated with nosocomial infections, which are responsible for up to 10% of these infections and some species have been described as causing outbreaks worldwide (García‐Solache and Rice 2019; Guerin et al .…”
Section: Introductionmentioning
confidence: 99%
“…Disappearance of E. faecium and E. faecalis in this study remains unclear, but similar finding has been reported by Ayeni et al (2016). Even though, E. faecium and E. faecalis rank as the second and third most important nosocomial pathogens worldwide (Zhang et al, 2017;Ramos et al, 2020), other species of Enterococcus should not be neglected. With the ability to acquire and transmit antibiotic resistant genes to other species, it poses a significant treatment challenge which leads to increment of treatment failure, relapse, and higher rates of mortality.…”
Section: Discussionmentioning
confidence: 99%